2020
DOI: 10.3892/etm.2020.8978
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme gene D-allele and the severity of coronary artery disease

Abstract: Coronary artery disease (CAD) is the first cause of morbidity and mortality worldwide. An important goal is to diagnose patients in early stages, in order to reduce acute cardiovascular events. The angiotensin-converting enzyme (ACE) is an important element for the cardiovascular system, through its actions on hydro-salin balance and vascular tone. ACE polymorphism consists of insertions (I)/deletions (D) and there are 3 genotypes: II, ID, DD. It is speculated that the DD genotype may be a genetic basis for se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Similar results were reported by MM et al [ 46 ], which showed a significant correlation of ACE2-I/D genotypes with respect to age ( p < 0.035). On the other hand, there was a study done by Maria-Cristina Vladeanu et al [ 47 ] that reported no statistically significant differences. Moreover, the results showed that there is no association between ACE2-rs4646994 I/D genotypes and the gender of patients with a ( p < 0.33), and the majority of them were males.…”
Section: Discussionmentioning
confidence: 93%
“…Similar results were reported by MM et al [ 46 ], which showed a significant correlation of ACE2-I/D genotypes with respect to age ( p < 0.035). On the other hand, there was a study done by Maria-Cristina Vladeanu et al [ 47 ] that reported no statistically significant differences. Moreover, the results showed that there is no association between ACE2-rs4646994 I/D genotypes and the gender of patients with a ( p < 0.33), and the majority of them were males.…”
Section: Discussionmentioning
confidence: 93%
“…Chen et al showed that acute coronary syndrome patients with the DD genotype have a 3.87-fold increased risk of stenosis in three coronary vessels, a 3.08-fold higher risk of stenosis of the left anterior descending artery, and a 3.07-fold higher risk of anterior wall infarction ( 6 ). Another study also indicated that the D allele was associated with the number of stenosed coronary arteries, especially its interaction with cardiovascular risk factors, such as sex (male), age (>65 years old), hypertension, diabetes, obesity, and smoking ( 7 ). In a group of 647 patients who underwent elective coronary angiography, Borzyszkowska et al found a significant association between the ACE DD genotype and the Gensini score in men with high total cholesterol, high LDL cholesterol, and low HDL cholesterol levels ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to environmental factors, genetic components have been revealed to be associated with the severity of CAD in AMI patients. Recent research has shown that CAD severity is influenced by variations in the angiotensin-converting enzyme ( ACE ) gene ( 6 , 7 ). ACE, an important component of the renin-angiotensin-aldosterone system, converts angiotensin I to angiotensin II and inactivates bradykinin via the kallikrein-kininogen system ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV infected patients often suffer from cardiac diseases as well as sudden death [121]. Amara et al, have shown that several risk factors had significant effects on CAD, including diabetes and dyslipidemia [122], in addition to gender, age, family history, smoking and genetic factors [123,124].…”
Section: Covid-19 and The Cardiovascular Systemmentioning
confidence: 99%
“…The RAS plays a role in cardiovascular homeostasis and hemodynamics, the reason for which is the special interest that has been accorded to its role in developing CVD [120], mostly due to some allelic variants in gene encoding for the RAS components [122,127]. Some mutations in these genes might influence the initiation and the outcome of CAD [124]. Essential hypertension, for example, is related to some genetic mutations in RAS components, such as the AT1R gene, and to angiotensinogen (AGT) M235T and ACE I/D polymorphisms [38].…”
Section: Covid-19 and The Cardiovascular Systemmentioning
confidence: 99%